Identification and Strategy of Leading Sector Development in The Migrant Workers Area in the Framework of Expanding Employment Opportunities - Yeni Nuraeni (AIBPM Publisher, 2019)
The unemployment rate in Indonesia is still high, dominated by a low-educated workforce. One solution to reduce the unemployment rate is to send workers abroad. Problems often occur with migrant workers in the informal sector, due to the minimal level of protection from the user country so as from the Indonesian government. The Indonesian government issued a policy to limit the sending of migrant workers in the informal sector, especially to middle eastern countries. This policy brings the consequences for the Indonesian government to provide alternative employment opportunities in the country. This study aims to identify leading sectors and analyze their development strategies. The development of leading sectors is expected to expand employment opportunities for local communities thereby reducing interest in working abroad, especially in the informal sector. Research uses quantitative and qualitative approaches. Data analysis using the Analysis Hierarchy Process (AHP) method. Data collection was carried out in Cilacap Regency, Central Java Province, as the largest regency for sending migrant workers in Central Java. The results showed the leading sectors in Cilacap Regency were the Agriculture and Processing Industry Sector. As for the development strategy, the most important factor is the development of human resources and the development / management of natural resources. Short-term Development Plans and Long-Term Development The Cilacap Regency Government must focus on leading sectors